2010
DOI: 10.1590/s1807-59322010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum paraoxonase and arylesterase activities in ankylosing spondylitis patients

Abstract: OBJECTIVESThe aim of this study was to investigate the activities of serum paraoxonase and arylesterase in patients with ankylosing spondylitis with respect to those of healthy controls, to assess whether these enzyme levels are related to disease activity and functional capacity.METHODSThe study included 32 patients with ankylosing spondylitis whose diagnoses were made according to the modified New York criteria as well as 25 healthy controls matched for age and sex. The Bath Ankylosing Spondylitis Disease Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 27 publications
0
33
2
Order By: Relevance
“…e signi cantly decreased PON1 activity observed in this study may re ect the increased consumption of antioxidant activity resulting from chronic in ammation and oxidant stress. Contrary to our results, Erdem et al reported no di erence in PON or arylesterase levels between AS patients and controls, but this may have been the result of di erent study techniques and/or shorter disease duration [34]. On the other hand, PON1 activity was found to be negatively correlated with disease duration, suggesting that PON1 is consumed as the disease progresses and chronic in ammation continues, which possibly is indicative of increased LDL oxidation and subsequent atherosclerosis.…”
Section: Discussioncontrasting
confidence: 99%
“…e signi cantly decreased PON1 activity observed in this study may re ect the increased consumption of antioxidant activity resulting from chronic in ammation and oxidant stress. Contrary to our results, Erdem et al reported no di erence in PON or arylesterase levels between AS patients and controls, but this may have been the result of di erent study techniques and/or shorter disease duration [34]. On the other hand, PON1 activity was found to be negatively correlated with disease duration, suggesting that PON1 is consumed as the disease progresses and chronic in ammation continues, which possibly is indicative of increased LDL oxidation and subsequent atherosclerosis.…”
Section: Discussioncontrasting
confidence: 99%
“…PON1 (paraoxonase activity, EC 3.1.8.1) was named after its ability to hydrolyze the organophosphate substrate paraoxon, that is the toxic metabolite of the insecticide parathion [5]. It is produced by the liver and is associated with HDL particles and is known to modulate the antioxidant and anti-inflammatory role of high density lipoprotein (HDL) [6] [7]. Paraoxonase (PON) family consists of PON1, PON2, and PON3 located on chromosome 7q21,3-22.1.…”
Section: Introductionmentioning
confidence: 99%
“…[5] PON1 is a calcium dependent esterase associated exclusively with HDL [8]. PON1 has 3 known enzymatic molecules including PON, arylesterase and dyazoxonase [7]. Serum PON1 also hydrolyzes proinflammatory oxidized lipids which is present in oxidized low density lipoprotein and ruins their atherogenic characteristics [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraoxonase-1 hydrolyzes organophosphates such as paraoxon, hydrolyzes aromatic esters such as phenylacetate, and also decreases the accumulation of lipid peroxidation products. Serum PON1 acts in conjunction with ARE to function as a single enzyme having lipophilic antioxidant characteristics [10] . To our best knowledge, PON1 and ARE activities in cow plasma has not been evaluated during the estrous cycle until now.…”
Section: Introductionmentioning
confidence: 99%